2020
DOI: 10.1093/gerona/glaa017
|View full text |Cite
|
Sign up to set email alerts
|

Informal Caregiving, Chronic Physical Conditions, and Physical Multimorbidity in 48 Low- and Middle-Income Countries

Abstract: Background The health of the caregivers is crucial to sustain informal care provision, while multimorbidity is an important health risk concept. However, studies on the association between informal caregiving and physical multimorbidity are currently lacking. Therefore, we investigated this association in adults from 48 low- and middle-income countries (LMICs). Method Cross-sectional data from 242,952 adults (mean age 38.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [ 26 , 59 ] and smoking [ 6 , 7 , 60 ] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [ 61 , 62 ]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [ 63 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [ 26 , 59 ] and smoking [ 6 , 7 , 60 ] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [ 61 , 62 ]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [ 63 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [26,59] and smoking [6,7,60] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [61,62]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [63][64][65].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, this study found that caregivers had a high level of demand and difficulty in their role [ 8 , 9 ]. The patterns of informal caregiving highlighted in this study demonstrated that people with a moderate to severe TBI are supported by both family and paid support, noting that 12 of the 29 people with TBI had some financial assistance through no-fault insurance or compensation systems.…”
Section: Discussionsupporting
confidence: 92%
“…The considerable burden experienced by caregivers has been long acknowledged [ 8 , 9 , 10 ] and has been shown to increase with time [ 11 , 12 ]. In addition, the perceived burden for caregivers of adults with TBI has been suggested to be higher when compared to caregivers for adults with other conditions such as dementia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%